2021
DOI: 10.46847/ujmm.2021.2(2)-005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological analysis of the structure of combat surgical injury during Antiterrorist operation / Joint Forces Operation

Abstract: I Introduction. In generalizing the experience of providing medical care to the wounded in armed conflicts, a special place belongs to the analysis of the magnitude and structure of casualties, which depend on the conditions, forms and methods of hostilities. The purpose. Conduct a clinical and epidemiological analysis of the proportion of gunshot and mine injuries in the structure of combat surgical trauma during the Anti-terrorist operation / Joint Forces operation. Materials and methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 5 publications
0
6
0
9
Order By: Relevance
“…На сьогодні вибухові ушкодження виділяють в самостійну категорію сучасної бойової травми. У сучасних збройних конфліктах зростає питома вага невогнепальних травм, зокрема закриті травми [3,4,10].…”
Section: коморбидные заболевания у военнослужащих -участников совреме...unclassified
See 1 more Smart Citation
“…На сьогодні вибухові ушкодження виділяють в самостійну категорію сучасної бойової травми. У сучасних збройних конфліктах зростає питома вага невогнепальних травм, зокрема закриті травми [3,4,10].…”
Section: коморбидные заболевания у военнослужащих -участников совреме...unclassified
“…Вибухова травма становила 12,2-50,8%, уражених з нетяжкою бойовою травмою було 36,5%. За локалізацією на бойову травму голови припадало 31,9%, закрита черепно-мозкова травма (ЗЧМТ) зустрічалась у 43,4% бойової нейрохірургічної травми і 12,8-25,2% всієї бойової травми, акубаротравму було діагностовано у 96,1% поранень ЛОР-органів [4,10].…”
Section: коморбидные заболевания у военнослужащих -участников совреме...unclassified
“…According to the 2014-2019 analysis, limb injuries account for between 52.3% and 60.1% of combat casualties. Gunshot fractures of long bones with widespread soft tissue defects and damage of large blood vessels and nerves occurred in 32.5-39.8% of the injured, and as a component of severe polytrauma, gunshot injuries of the extremities were observed in 67.5-74.4% of the injured [4]. Most of the injured had shrapnel injuries of their limbs (80.4%), of which 70.6% had penetrating, isolated or multiple injuries [5].…”
Section: Introductionmentioning
confidence: 99%
“…Khomenko with co-author. (2021) concluded that in the structure of combat sanitary losses, combat injury to the limbs ranges from 52.3 to 60.1% [1]. Among those wounded in the limb, soft tissue defects requiring plastic closure are present in 64.9-68.2% [2].…”
Section: Introductionmentioning
confidence: 99%